Bacterial DNA Induced TNF-alpha Expression in Buffaloes (Murrah) in Comparison to that of Cross Breed Cattle - Nisha, P.; Thanislass, J.; Antony, P.X.; Mukhopadhyay, H.K.; Reddy, K.V. Subba (Journal of Buffalo Science, 2013)
Buffaloes are generally considered to be disease resistance. But systematic studies to understand the underlying mechanism of disease resistance in buffaloes in comparison to that of cattle are scanty. Therefore, the present study was undertaken to study the immune response in terms of TNF-α expression in PBMCS isolated from buffaloes in comparison to that of cattle. PBMCs were isolated from blood collected from healthy buffaloes and cross breed cattle and incubated with bacterial (E.coli) DNA at different concentration for a different period of time. Total RNA was isolated and mRNA expression of TLR9 and TNF-α was studied. Expression of actin gen was studied as positive control. Incubation of PBMCs with bacterial DNA resulted in the expression of TLR9 in both, buffaloes and cattle. But, the expression of TNF-α was seen only in the case of buffaloes and the level was found to increase with the increase in bacterial DNA concentration and time. Thus this study reports the inherent difference in the immune response of buffaloes in comparison to that of cattle.